Green human resources management of the small and micro-enterprises in Indonesia - Raniasari Bimanti Esthi; Indra Setiawan (Enrichment : Journal of Management, 2023)
The sustainability of an environmentally sound business raises the active role of human resources in society, and a running company can be social, economic, and environmental impacts in the long term. In running an environment-based business, small and micro enterprises (SMEs) need to integrate business management and human resources, starting from aligning business goals and preparing corporate culture to concern for welfare. One of the methods used to manage environmental businesses is by implementing Green Human Resource Management (GHRM). The aims of this study were 1) to determine the effect of GHRM on job satisfaction, 2) to determine the effect of GHRM on employee performance, and 3) to determine the effect of GHRM on corporate culture. The population in this study were all SME employees engaged in environment-based businesses. Then the sampling technique was carried out by purposive random sampling. The analytical method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results of this study show that GHRM has a positive and significant effect on job satisfaction, employee performance, and corporate culture.